Looking to the east and the west: the double-attachment strategy used by the Hong Kong government to develop welfare to work measures for lone parents. Issue 2 (June 2014) - Yu, Sam W.K.; Chau, Ruby C.M.; Boxall, Kathy; Chung, Wind C.Y.
Abstract : This article discusses how the Hong Kong government used a double-attachment strategy to develop welfare to work measures for lone parents; and demonstrates how this discussion could contribute to the study of the cultural and political economy perspectives on East Asian welfare regimes. It shows that the Hong Kong government developed welfare to work measures with reference not only to the New Deal for Lone Parents in the UK, but also to certain traditional Chinese principles. In view of the Hong Kong government's attempt to attach its welfare policies to its own tradition and to the thinking of Western world, it is argued that both cultural and political economy perspectives are significant in the study of East Asian welfare regimes. Moreover, it is important to have a realistic understanding of the uniqueness of East Asian countries in the ways they organize welfare even though there are similarities with Western countries.